2021
DOI: 10.9734/jpri/2021/v33i631191
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Platelet Rich Plasma Injection Effect on Knee Osteoarthritis in Elderly: Single Dose versus Double Dose Randomized Clinical Trial

Abstract: Objective: This study aims to evaluate the effect of platelet rich plasma (PRP) and compare between single and double dose regimens among patients diagnosed with osteoarthritis admitted to the orthopedic department of Al Qassimi Hospital Sharjah, United Arab Emirates. Methods: 200 patients were allocated into two groups in this randomized clinical trial. Patients were chosen to participate in this study after an informed consent. The trial took place at the Al Qassimi Hospital Sharjah, United Arab Emirat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…found no difference in WOMAC scores between patients who received one versus three PRP injections, over a six month period. This is similarly reflected by a 2021 study that observed no additional benefit of a second injection administered two weeks after a first injection 24 . Therefore, there is no concrete number, or spacing, of PRP injections recommended in the symptomatic management of knee osteoarthritis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…found no difference in WOMAC scores between patients who received one versus three PRP injections, over a six month period. This is similarly reflected by a 2021 study that observed no additional benefit of a second injection administered two weeks after a first injection 24 . Therefore, there is no concrete number, or spacing, of PRP injections recommended in the symptomatic management of knee osteoarthritis.…”
Section: Discussionmentioning
confidence: 99%
“…This is similarly reflected by a 2021 study that observed no additional benefit of a second injection administered two weeks after a first injection. 24 Therefore, there is no concrete number, or spacing, of PRP injections recommended in the symptomatic management of knee osteoarthritis. Currently, in Australia, PRP injections are not covered by Medicare, resulting in high out of pocket costs for patients.…”
Section: Discussionmentioning
confidence: 99%